Pathogenesis of domestic pigs submitted to mycobacterial sensitizations previous to experimental infection with Mycobacterium bovis - Cuerda, Maria Ximena; Colombatti Olivieri, Maria Alejandra; Gravisaco, María José; Marfil, Maria Jimena; Barandiaran, Soledad; Sevilla, Iker A.; Garrido, Joseba M.; Moyano, Roberto Damian; Zumarraga, Martin Jose; Romano, Maria Isabel; Juste, Ramón A.; Santangelo, María De La Paz (INIA (España), 2022)
Aim of study: To demonstrate the virulence of a Mycobacterium bovis local pig isolate in order to contribute to a better understanding of the pathological and immunological consequences of M. bovis infection in previous sensitized animals.